(Nu^ENIE O ^ASTQH RE^I ARMQNSKOGO QZYKA (B/s - d; (NeREWANSKIJ GOSUDARSTWENNYJ UNIWERSITETs ((NeREWAN (B:s (NiZD(B-(NWO eREW(B. (NUN(B-(NTA(B,s, 1988)
(NbIBLIOGR(B.: (NS(B. 419-427 (170 (NNAZW(B.)s
(NuKAZ(B. (NLI^(B. (NIMEN(B: (NS(B. 428-431s
Keywords: (NaRMQNSKIJ QZYKs -- (NgRAMMATIKA ISTORI^ESKAQs